Relações retóricas sinalizadas pelas estratégias de correção e de parafraseamento em elocuções formais - Cassim, Fernanda Trombini Rahmen (2014)
This work aimed to investigate paraphrase and correction strategies in formal utterances. In addition to noting the main semantic features of these strategies - such as the operationalization of relations, the adjacency and the grammatical marking -, it is also possible to find some rhetorical relations established by these strategies. The research was based on the functionalist assumptions of the Rhetorical Structure Theory (RST), a descriptive theory which has as its object of study the relations established between the parts of the text, and in Textual-Interactive Grammar. The corpus of the research consisted of five classes that are part of the Group of Functionalist Research in the North/Northwest of Paraná database (FUNCPAR). The utterances were transcribed according to the standards established by Project of Educated Urban Standards (NURC) and divided into intonation units. With the quantitative analysis of the corpus, it was possible to find mostly: adjacent paraphrases, self-initiated paraphrases, parallel paraphrases and rhetorical relations of evidence and elaboration (when the paraphrases were expansive), of core-satellite reformulation (when the paraphrases were parallel) and of summary (when the paraphrases were restrained). Therewith, it was possible to find that there was no recurrence of rhetorical relations in accordance with the semantics of paraphrases. It was also noted that the expressive resources used in the paraphrases had well-defined goals, according to the context and with the effects intended by the speaker. About the correction, it can be noticed that, in its entirety, they were self-initiated corrections, and for the most part, they were rectifying corrections of linguistic aspect, marked by interruption with and without repetition and with words totally verbalized. Furthermore, it was possible to observe that, according to the class, there were information and corrections seen from an enunciative perspective. Usually, when the class was about a subject on which it was required a positioning (such as a geography class, for instance), there were more modalizations at the time of exchanging EF (source utterance) for ER (reformer statement). As for the rhetorical relations, it was necessary to resume the relation of correction presented by Antonio and Cassim (2012), which seeks to replace the content present in the core with the content present in the satellite. This relation was established in every strategy of correction presented in the corpus. Through this research, it is expected to be able to collaborate with future academic analysis involving the RST and the formulation of spoken text strategies, especially the correction and the paraphrase.